Continuation Rates of the 52-mg Levonorgestrel-releasing Intrauterine System according to the Primary Reason for its Use - Laura Miranda; Maria Helena de Sousa; Anibal Faundes; Cássia Juliato (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To evaluate whether continuation rates with the 52-mg levonorgestrelreleasing intrauterine system (LNG-IUS) up to 5 years after placement differed between women using the method exclusively for contraception and those using the device for medical reasons alone. Methods A retrospective cohort study was conducted in a family planning clinic with 5,034 LNG-IUS users: 4,287 using the method exclusively for contraception and 747 for medical reasons alone. The continuation rate at 1 to 5 years of use was calculated by life table analysis. Results Initially, the continuation rate was significantly higher in the contraception group: 85.8 versus 83.4 and 77.4 versus 76.0 per 100 women-years in the 1st and 2nd years of use, respectively. There were more discontinuations due to bleeding/spotting in the medical reasons group in the first two years. The discontinuation rate according to reason for use was not significantly different from the third to the fifth year of use. No women discontinued due to amenorrhea in either group. Conclusion The continuation rate was significantly higher in the contraception group in the first two years of use. Amenorrhea was not a reason for discontinuation in either group, suggesting that counselling in this respect was adequate. Nevertheless, counselling could perhaps have been better with regards to the expected long period of bleeding and spotting in the first two years after placement.